2018
DOI: 10.1007/s00299-018-2338-x
|View full text |Cite
|
Sign up to set email alerts
|

OsNDUFA9 encoding a mitochondrial complex I subunit is essential for embryo development and starch synthesis in rice

Abstract: Loss of function of a mitochondrial complex I subunit (OsNDUFA9) causes abnormal embryo development and affects starch synthesis by altering the expression of starch synthesis-related genes and proteins. Proton-pumping NADH: ubiquinone oxidoreductase (also called complex I) is thought to be the largest and most complicated enzyme of the mitochondrial respiratory chain. Mutations of complex I subunits have been revealed to link with a number of growth inhibitions in plants. However, the function of complex I su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Rice endosperm is known to be an excellent system for elucidating how gene networks regulate starch synthesis and amyloplast development (Nelson and Pan 2003;Satoh and Omura 1981), so various mutants with defective endosperm have been screened for further research. In terms of appearance, oury endosperm mutants can generally be divided into two types: completely oury endosperm mutant (such as FLO13 (Hu et al 2018), FLO14 (Xue et al 2019), FLO16 (Teng et al 2019) and FLO18 (Yu et al 2020)) and partially oury endosperm mutant (such as FLO4 (Kang et al 2005), FLO7 and FLO15 (You et al 2019)). Interestingly, similar to previously reported o7 mutant, the peripheral region of o19 mutant grain also appeared oury-white (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Rice endosperm is known to be an excellent system for elucidating how gene networks regulate starch synthesis and amyloplast development (Nelson and Pan 2003;Satoh and Omura 1981), so various mutants with defective endosperm have been screened for further research. In terms of appearance, oury endosperm mutants can generally be divided into two types: completely oury endosperm mutant (such as FLO13 (Hu et al 2018), FLO14 (Xue et al 2019), FLO16 (Teng et al 2019) and FLO18 (Yu et al 2020)) and partially oury endosperm mutant (such as FLO4 (Kang et al 2005), FLO7 and FLO15 (You et al 2019)). Interestingly, similar to previously reported o7 mutant, the peripheral region of o19 mutant grain also appeared oury-white (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…FLO10 encodes a pentatricopeptide repeat protein that acts as a chaperone in the trans -splicing of mitochondrial nad1 intron 1 during endosperm development ( Wu et al, 2019 ). It has also been shown that a mitochondrial complex I subunit (FLO13) controls grain size, grain quality and thousand grain weight and is associated with the respiratory electron chain complex of the mitochondria ( Hu T. et al, 2018 ). A class I glutamine amidotransferase named FLO19, has been reported to affect grain quality and the expression of other amyloses ( Lou et al, 2021 ).…”
Section: Genetic and Molecular Determinants Of Grain Weight Through Size Determinationmentioning
confidence: 99%
“…FLO13, known as OsNDUFA9, encodes subunit mitochondrial complex I. Loss of OsNDUFA9 changes the mitochondrial structure and greatly impairs the development of rice endosperm (Hu et al, 2018). FLO16, known as OsCMDH, encodes an NAD-dependent cytosolic malate dehydrogenase.…”
Section: Flo Genes Play Important Roles In Endosperm Development Of Ricementioning
confidence: 99%